Influence of dates of sowing and environmental factors on collar rot of okra - A.K. JHA, S.C. DUBEY and (Indian Phytopathology, 2002)
Field trials were conducted in the plateau region of Bihar, India, in 1994-95 to assess the effects of planting date (1 Jan.-17 Dec.) and environmental factors (maximum and minimum temperatures, relative humidity and rainfall) on seed germination, pre- and post-germination mortality and development of collar rot disease (Macrophomina phaseolina) in okra cv. Prabhani Kranti. Results indicated that later planting was associated with the lowest incidence of collar rot and highest crop yields.